2015
DOI: 10.1530/rep-14-0446
|View full text |Cite
|
Sign up to set email alerts
|

Tri-ortho-cresyl phosphate induces autophagy of rat spermatogonial stem cells

Abstract: Tri-ortho-cresyl phosphate (TOCP) has been widely used as plasticizers, plastic softeners, and flame retardants in industry and reported to have a deleterious effect on the male reproductive system in animals besides delayed neurotoxicity. Our preliminary results found that TOCP could disrupt the seminiferous epithelium in the testis and inhibit spermatogenesis, but the precise mechanism is yet to be elucidated. This study shows that TOCP inhibited viability of rat spermatogonial stem cells in a dose-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 43 publications
4
22
0
Order By: Relevance
“…TOCP has been shown to induce autophagy of human neuroblastoma SH‐SY5Y cells . We also found that TOCP could induce autophagy of mouse spermatogonial stem cells and mouse Leydig TM3 cells . In the present study, we found that TOCP exposure induced autophagic cell death of mouse ovarian granulosa cells, which was in accordance with our previous results .…”
Section: Discussionsupporting
confidence: 92%
“…TOCP has been shown to induce autophagy of human neuroblastoma SH‐SY5Y cells . We also found that TOCP could induce autophagy of mouse spermatogonial stem cells and mouse Leydig TM3 cells . In the present study, we found that TOCP exposure induced autophagic cell death of mouse ovarian granulosa cells, which was in accordance with our previous results .…”
Section: Discussionsupporting
confidence: 92%
“…In this study we found that TOCP treatment significantly upregulated the levels of Beclin‐1, Atg5 proteins and the ratio of LC3 II/LC3 I in almost all doses of TOCP‐treated groups on GD 13 and 400 mg/kg/day TOCP‐treated group on GD 8. Our results above were in accordance with Liu's findings that exposed to 0 to 0.5 mM TOCP, mice Leydig TM3 cells had elevated expression levels of LC3 II/LC3 I, Atg5, and Beclin1 . Moreover, previous studies also demonstrated that the autophagy‐related proteins Atg5, Beclin‐1, and LC3 II/LC3I expression were markedly increased in rat spermatogonial stem cells after exposure to 0 to 1.0 mM TOCP for 48 hours .…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, male mice orally administered different concentrations of TOCP for 28 days showed hepatocellular injury, accompanied by the increase of MDA and decrease of SOD and glutathione . It suggested that the cell damage caused by TOCP was partly mediated by the increase of oxidative stress . On the other hand, our study also showed that the levels of CAT and SOD in placental tissues were increased significantly in the high dose group on GD 8, which may be a compensatory mechanism beneficial to recover the body damage when exposed to TOCP during early pregnant process.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In the rat, approximately half of all germ cells die at parturition (Roosen-Runge and Leik 1968), and apoptosis of male germ cells has been detected even while these cells are mitotically arrested (Coucouvanis et al 1993). Autophagy has also been recently demonstrated in SSCs following the addition of a plasticizer in vitro (Liu et al 2015). Treatment with angiogenic VEGFA164 has been demonstrated to promote germ cell survival, whereas inhibition of VEGFA signal transduction results in germ cell loss in cultured bovine testis explants (Caires et al 2009).…”
Section: Introductionmentioning
confidence: 98%